How does family background influence students' choice of subjects for the National College Entrance Examination? - Fang, Fang; McCall, Brian; Zhong, Binglin (Higher education research and development, 2022)
The National College Entrance Examination (NCEE) is a high-stakes test in China that determines which higher education institution an individual can attend. Since 2014, China has launched a comprehensive reform pilot of the NCEE in Zhejiang and Shanghai, allowing students more flexibility in their subjects' choice. This study examines the influence of family background on students' choice of subjects in this new NCEE. Using survey data from academic high school students in Zhejiang province, we find that students from urban as compared to rural families are more likely to want to be tested on science subjects and less likely to want to be tested on politics. Students from high-income as compared to low-income families are more likely to choose politics and history and less likely to choose physics and chemistry test subjects.